Association of Biochemical Anemic Markers in STEMI and NSTEMI Patients – A Retrospective Study: Life Sciences-Medical Science - Aishwarya, S.; Vasanthan, M.; Vinodhini, V.M.; P, Renuka.; Dhandapani, V.E. (International Journal of Life Science and Pharma Research, 2022)
Body iron stores and its significant association with the increased risk of cardiac disease was first time reported by the National Health and Nutrition Examination Survey. There are several molecular mechanisms and discrete pathways involved in developing Myocardial Infarction (MI) as a result of increased body iron store. Various studies showed that there lies a significant association between serum iron and serum ferritin with the MI, but to the best of our knowledge studies have not focused on the difference in their levels in STEMI and NSTEMI patients. Hence, the aim of the study is to associate the levels of iron and ferritin with STEMI and NSTEMI patients and the objective of the study is to investigate and associate the iron, ferritin and lipid profile parameters among STEMI and NSTEMI patients. The cross-sectional study recruited 75 individuals who lie in the age group of 25-55 years. The participants were divided into three groups with 25 participants in STEMI, 25 in NSTEMI (based on the ECG findings and cardiologist findings) and 25 healthy participants who are age and sex-matched as controls. The blood sample was obtained from the participants and analysed for the following biochemical parameters: CK - MB, iron, ferritin, and lipid profile. The data was analysed using SPSS software and represented as mean and SD. One-way ANOVA, Pearson’s correlation and odds calculation were carried out. For all statistical test p value <0.05 were considered as significant. It is found that serum iron and ferritin were significantly elevated in STEMI individuals compared to NSTEMI and controls. But the lipid profile levels were increased in NSTEMI individuals. It is found that individuals with increased levels of iron and ferritin are at high risk of developing STEMI and NSTEMI compared with controls. Iron and ferritin were significantly elevated in STEMI individuals compared to NSTEMI individuals. In NSTEMI group lipid profile levels were increased and is associated with ferritin levels compared to STEMI group. Independent to the type of MI, individuals with high levels of serum iron and ferritin are at higher risk of developing myocardial infarction.